The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1752-153x-7-57
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of anti-cancer steroid exemestane and cytotoxicity of its metabolites against cancer cell lines

Abstract: BackgroundMicrobial transformation of steroids has been extensively used for the synthesis of steroidal drugs, that often yield novel analogues, not easy to obtain by chemical synthesis. We report here fungal transformation of a synthetic steroidal drug, exemestane, used for the treatment of breast cancer and function through inhibition of aromatase enzyme.ResultsMicrobial transformation of anti-cancer steroid, exemestane (1), was investigated by using two filamentous fungi. Incubation of 1 with fungi Macropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Several synthesis methods have been published, however, none of them is from Vietnam. [13][14][15] Moreover, at present, most of available Exemestane contained drugs in Vietnam are imported at quite high price, not yet suitable for our general low income situation. In order to obtain domestically produced Exemestane, herein, we report the two-step synthesis protocol of Exemestane from the commercial available compound androst-4-ene-3,17-dione (1), using the published method from Annen.…”
Section: Introductionmentioning
confidence: 99%
“…Several synthesis methods have been published, however, none of them is from Vietnam. [13][14][15] Moreover, at present, most of available Exemestane contained drugs in Vietnam are imported at quite high price, not yet suitable for our general low income situation. In order to obtain domestically produced Exemestane, herein, we report the two-step synthesis protocol of Exemestane from the commercial available compound androst-4-ene-3,17-dione (1), using the published method from Annen.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolite 228 was formed mainly through hydroxylation of exemestane by Fusarium lini (NRRl 2004) and 229-231 were formed as a result of reduction of 17-oxo group of exemestane by Macrophomina phaseolina (KUCC 730). In vitro cytotoxicity studies against Hela and PC-3 cancer cell lines revealed that metabolite 228 was fairly cytotoxic against both the cell lines with IC 50 values of 16.83 and 24.87 µM,respectively [166]. In continuation to their efforts to design and synthesize novel steroidal aromatase inhibitors, Varela et al recently explored anti-aromatase activity of exemestane metabolites 231[166] and 232-234 (Figure 68) in both human microsomes and MCF-7aro cell line.…”
mentioning
confidence: 97%
“…In vitro cytotoxicity studies against Hela and PC-3 cancer cell lines revealed that metabolite 228 was fairly cytotoxic against both the cell lines with IC 50 values of 16.83 and 24.87 µM,respectively [166]. In continuation to their efforts to design and synthesize novel steroidal aromatase inhibitors, Varela et al recently explored anti-aromatase activity of exemestane metabolites 231[166] and 232-234 (Figure 68) in both human microsomes and MCF-7aro cell line. Transformation of one double bond of A or B ring of exemestane (5) into epoxide group resulted into two metabolites i.e.…”
mentioning
confidence: 97%
“…The cytotoxic activity of samples was determined by the MTT assay, according to Baydoun and Mosmann with slight modification (Baydoun et al, 2013;Mosmann, 1983), on two cancer cell lines, i.e. HeLa (cervical cancer cells) and PC-3 (prostate cancer cells).…”
Section: Anticancer Assaymentioning
confidence: 99%
“…Finally, IC50 values were calculated. Doxorubicin was used as the positive control (Baydoun et al, 2013).…”
Section: Anticancer Assaymentioning
confidence: 99%